THE SOCIAL ORGANIZATION OF HEALTH CARE, AMERICAN MEDICINE IN THE 21ST CENTURY - Anderson, James (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
The major objective of this course is to critically examine the organization of health and medical care from a sociological perspective. The focus will be on: (1) Health and Illness in American Society (2) The health care professions (3) The professional and occupational roles of these practitioners (4) The organizational contexts in which they are trained and provide care (5) The cost and financing of health care in the U.S. (6) The politics of health care delivery (7) The organization of health care in other countries